A Rádio Inconfidência nos tempos do auditório: considerações sobre os gêneros musicais no acervo de partituras - Guilherme Dias Melo Carvalho (2014)
By the advent of the Radio in Brazil it generated a great deal of changes in cultural values in the Brazilian society in the 1920s. As it became an important tool for communication and social integration, daily habits were innovated and it also contributed to the dissemination of several kind of arts. Throughout the 1930s, many Brazilian Radio Stations were founded and reached its development golden period around the 1950s when musical groups and artists from different regions of Brazil were presented in auditorium stations and broadcasted live across the country. Radio Inconfidência in the city of Belo Horizonte was founded in 1936, and had a large infrastructure to welcome artists and promote various musical acts with the involvement of several orchestras and singers performed in the auditorium programmes. The score collection of the station consists of many arrangements in various musical genres, and it was the result of an intense artistic activity and music production in the period between 1950 and 1960 which were performed in the auditorium programmes by the musical groups from the Radio. With all the information in the collection arrangements retated to musical genres, the instrumentation used by orchestras and the name of musicians, such as arrangers, singers and conductors were able to combine indicative elements for arrangements production and performance.The interviews with the characters of that time, for instance the radio announcer Ricardo Parreiras and the musician and pianist Hely Ferreira Drummond ,we could better understand the context about the arrangements performance in the auditorium programmes of the Inconfidência Radio Station. Assuming that the genre is considered a cultural symbol associated with musical groups, places and historical periods, this study sought to the possibility of a relationship between musical genres collection of scores and the performance of musical arrangements entertained by Radio groups in talk shows. In order to verify a change of direction in the musical genre, the samba was chosen to be discussed in the context of the hearings of talk shows, because of the prevalence of this musical genre in the collection of scores. To come to this conclusion, it was necessary the knowledge of different orchestras which acted in Radio stations, the room where the performances occurred and the radio programmes where the arrangements were executed.